Scenario analysis of online food supply chains - Anne Beckmann (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: For a long time, online food retail, especially in Germany, lagged strongly behind other e-commerce industries. The COVID-19 pandemic gave this market an unforeseen boost in demand. Nevertheless, numerous problems still exist in the industry, such as lack of profitability, staff shortages, and product returns. Identifying possible future developments can help to design meaningful strategies for the fulfillment within online food supply chains. Methodology: The scenarios are built using Porter's Five Forces in combination with a STEPE analysis examining socio-cultural, technological, economic, political, and ecological factors. The findings are validated and ranked by four interviews with experts working in the online food retail industry. Findings: The literature research and the assessment of the experts show that above all socio-cultural (e.g., customers' price sensitivity) and technological factors (e.g., warehouse automation) will be decisive for the future development of the industry. These are combined to form three scenarios (best-case, worst-case, focus on shelf-stable food). Implications for online food retailers are given for each scenario. Originality: This paper applies methods of trend and future research to the areas of online food retail and logistics and supply chain management research. In this area only little original scientific research exists.
urn:nbn:de:gbv:830-882.0161689; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; innovation management; technology management